Gambaran Manajemen Sumber Daya Manusia Pada Layanan Kesehatan di Indonesia: Sebuah Literature Review - Fuadi, Mirza Fathan (Universitas Ivet, 2025)
Human Resource Management (HRM) is a strategic component within the healthcare system that directly influences service quality and organizational performance. This review aims to identify and analyze literature discussing the roles, challenges, and strategies of HRM in the context of health services. The literature search was conducted through databases including PubMed, ScienceDirect, Directory of Open Access Journals (DOAJ), ResearchGate, Google Scholar, and Academia.edu using the keywords